A Comparative Analysis of Operational Risk Management Practices in UK Banks and Insurers - Toussaint, Richelle (2015)
The study seeks to provide a comparative analysis of the operational risks management practices in UK banks and insurance companies. For this analysis the FTSE 350 Investment and Retail banks together with Life and Non-Life insurers operating in the UK were considered totalling to seventeen firms. There is currently a dearth of literature on the operational risks management practices of financial institutions in general and where there is research available heavy emphasis is placed on banks and not insurance firms. The research was conducted by means of a survey to analyse the firms operational risk management practices as well as the challenges that market participants face in the implementation of an effective operational risk management system. Moreover, the study also examines how the implemented Basel II regulation has shaped the way in which banks conduct their operational risks function and how the forthcoming Solvency II regulation can impact the way that insurance companies develop their operational risk management framework to adhere to the guidelines of the decree.